EFFECT OF BREASTFEEDING ON ANTHROPOMETRIC PARAMETERS IN POSTNATAL GROWTH OF PRE-PUBERTAL MALE CHILDREN - Khan, Abdul Ghaffar; Iqbal, Tehseen; Faruqi, Muhammad Shahid; Khokhar, Abdul Rehman (Pakistan Journal of Physiology, 2017)
Background: Breastfed and bottle-fed children’s growth is not on the same pattern. This study was conducted to find out the effect of breast and bottle feeding on pre-pubertal children. Methods: This comparative study was conducted in the Department of Physiology, University of Health Sciences, Lahore. The study was conducted during the period from Oct 2013 to Apr 2015. A total number of 90 male pre-pubertal children were included in this study. Only male children were included to avoid bias of sex. Participants were selected from the school children of the locality around the University of Health Sciences (UHS) Lahore. They belonged to middle socioeconomic group. Their age range was 8–10 years, on the basis of history taken from parents of children. Participants were divided into two groups. Group-I, It included 45 male children having exclusive breastfeeding during the first year after birth. Group-II, It included 45 male children having exclusive bottle feeding during the first year after birth. Results: The median (Q1–Q3) weights were 27 Kg (25–29) and 25 Kg (22–29) in breastfed and bottle-fed groups respectively. The difference was considered significant with p=0.017. The median (Q1–Q3) heights were 133 Cm (130–137) and 130 Cm (122–136) in breastfed group and bottle-fed group respectively. The breastfed group children had significantly greater height (p=0.030) as compared with the bottle-fed group children. Conclusion: Breastfeeding has a positive effect on Height and weight of pre-pubertal children. Pak J Physiol 2017;13(3):15–7